IMPLEMENTASI MODEL PEMBELAJARAN PORTOFOLIO DALAM PENINGKATAN MUTU PEMBELAJARAN PAI (STUDI KASUS DI SDN CEMPAKAPUTIH KABUPATEN BANDUNG) - Dana Sujana; Husen Saeful Insan; Ahmad Sukandar (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The development of learning models is an unsolved problem in line with the complexity of environmental changes, both in terms of planning, implementation and assessment. Various learning models continue to be carried out but have not provided an optimal impact on improving the quality of PAI learning both in terms of process and results. The method used in this research is qualitative research, qualitative data analysis/processing techniques include three stages, namely: (1) data reduction; (2) data presentation; and (3) data verification. This study aims to obtain an overview of the Implementation of the Portfolio Learning Model. This study uses a qualitative naturalistic approach, the method uses a case study method with data collection techniques through interviews, documentation studies and observations. The results show that the use of the portfolio learning model can encourage the growth of students' enjoyment of the lesson, grow and increase motivation to do assignments, make it easier for students to understand lessons so that all components related to education must be optimized, one of which is the competence of teachers who are able to utilize various sources. in the presentation of the teaching and learning process. The learning process will be fun because students accept and give according to their abilities. The atmosphere of teaching and learning is fun, stimulating students to learn actively, creatively and effectively so that learning objectives are achieved optimally.